Testing the efficacy of Floragas against the eggs of lightbrown apple moth (Epiphyas postvittana) - Page-Weir, N.E.M.; Jamieson, L.E. (New Zealand Plant Protection, 2009)
In September 2008 lightbrown apple moth (Epiphyas postvittana) (LBAM) eggs were found in a shipment of flowers grown in the South Island which were destined for California USA This prompted a ban on New Zealand flower exports to the USA The aim of this investigation was to determine the efficacy of the insecticidal aerosol Floragas against LBAM eggs LBAM eggs (2 days) were treated with Floragas as per the label instructions Egg batches were assessed 5 and 12 days after fumigation Results indicated that fewer LBAM eggs were fertile following the fumigation treatment (712) than untreated eggs (897) 5 days after fumigation Only 154 of fumigated eggs hatched compared with 631 of untreated eggs 12 days after fumigation Fumigation with Floragas resulted in 846 mortality of all LBAM eggs